Centrifugal Differential Mobility Analysis—Validation and First Two-Dimensional Measurements - Rüther, Torben Norbert; Gröne, Sebastian; Dechert, Christopher; Schmid, Hans-Joachim (Powders)
To obtain a more comprehensive understanding of the specific properties of complex-shaped technical aerosols—such as partially sintered aggregates formed in combustion processes or structured particles resulting from complex synthesis processes—it is essential to measure more than a single equivalent size. This study examines a novel method for determining a two-dimensional distribution of two distinct particle properties within the size range from 50nm to 1000nm: the Centrifugal Differential Mobility Analyzer (CDMA). The CDMA enables the simultaneous measurement of both mobility and Stokes equivalent diameters, providing a detailed two-dimensional particle property distribution. This, in turn, allows for the extraction of shape-related information, which is essential for characterizing particles in terms of their chemical composition, reactivity, and other physicochemical properties. This paper presents a detailed evaluation of a first CDMA prototype. First, CFD simulations of the flow field within the classifier are presented in order to assess and understand non-idealities arising from the exact geometry. Subsequently, the transfer function is evaluated by particle trajectory calculations based on the simulated flow field. It can be demonstrated that the simulated transfer functions agree quite well with transfer functions derived from streamlines of an ideal flow field, indicating that the non-idealities in the classifying region are almost negligible in their effect on the classification result. An experimental determination of the transfer function shows additional effects not covered by the previous simulations, like broadening by diffusion and losses due to diffusion and precipitation within the in- and outlet of the classifier. Finally, the determined transfer functions are used to determine the full two-dimensional distribution with regard to the mobility and Stokes equivalent diameter of real aerosols, like spherical particles and aggregates at different sintering stages, respectively.
Keywords: centrifugal differential mobility analysis; 2D-measurement; particle characterization; moving reference frame CFD-simulation; transfer function

The Centrifugal Differential Mobility Analyser – concept and initial validation of a new device for measuring 2D property distributions - Rüther, Torben N.; Rasche, David B.; Schmid, Hans-Joachim (Aerosol Research)
Abstract. Usually for the characterization of nanoparticles, an equivalent property is measured, e.g. the mobility-equivalent diameter. In the case of non-spherical, complex-shaped nanoparticles, one equivalent particle size is not sufficient for a complete characterization. Most of the methods utilized to gain deeper insight into the morphology of nanoparticles are very time-consuming and costly or have bad statistics (such as tandem setups or TEM (transmission electron microscopy)/SEM (scanning electron microscopy) images). To overcome these disadvantages, a prototype of a new compact device, the Centrifugal Differential Mobility Analyser (CDMA), was built, which can measure the full 2D distribution of mobility-equivalent and Stokes equivalent diameters by classification in a cylinder gap through electrical and centrifugal forces. An evaluation method to determine the transfer probabilities is developed and used in this work to compare the measurement results with the theory for the pure rotational behaviour (like the Aerodynamic Aerosol Classifier) and the pure electrical behaviour (like the Dynamic Mobility Analyser). In addition, the ideal 2D transfer function was derived using a particle trajectory approach. This 2D transfer function is a prerequisite for obtaining the full 2D particle size distribution from measurements by inversion.

The POCS-Algorithm—An effective tool for calculating 2D particle property distributions via data inversion of exemplary CDMA measurement data - Rüther, Torben N.; Rasche, David B.; Schmid, Hans-Joachim (Journal of Aerosol Science)
Keywords: POCS; Projection onto convex sets; Data inversion; 2D distribution; CDMA; Centrifugal Differential Mobility Analyzer

Prediction of the transfer function for a centrifugal differential mobility analyzer by streamline functions - Rüther, Torben N.; Schmid, Hans-Joachim (Aerosol Science and Technology)

Polymer Suspensions under Uniaxial Extension – A novel Way to Produce Core-Shell-Particles? - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Influence of Dispersion Gas and Resulting Reaction Zone on the Particle Formation in Spray Flame Synthesis (Presentation) - Massopo, Orlando; Schmid, Hans-Joachim; Reddemann, Manuel; Kneer, Reinhold; Bieber, Malte

Untersuchung des Lösungsmitteleinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Einfluss der Zerstäubungsparameter auf die Partikelbildung und die Eigenschaften der Endproduktpulver (Studienarbeit) - El Gabbouhi, Abderazzak; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Entwicklung einer Datenbank hergestellter Nanomaterialien mittels Gasphasensynthese (Studienarbeit) - Reimer, Jens; Massopo, Orlando; Schmid, Hans-Joachim

Particle-induced Instabilities in Uniaxially Elongated Thermoplastic Polymer Blends - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Correlation between SLS-Powder processability and particle properties - Rüther, Moritz Johannes; Klippstein, Sven Helge; Schmid, Hans-Joachim (PARTEC International Congress on Particle Technology - Book of Abstracts)

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.

Large eddy simulation of iron oxide formation in a laboratory spray flame (Applications in Energy and Combustion Science)
Iron oxide nanoparticles are very interesting for many applications in different industrial sectors. A promising process to manufacture these nanoparticles is flame spray pyrolysis (FSP). A lack of understanding of the individual sub-processes in FSP makes it challenging to tailor nanoparticle properties. This work provides insights into the formation of iron oxide nanoparticles in a turbulent spray flame using Large Eddy Simulations (LES), which are based on a comprehensive model, including customized submodels. Highlights are the adaption of a turbulent combustion model and a bivariate hybrid method of moments for modeling nanoparticle dynamics. The work focuses on the SpraySyn burner, which is a standardized laboratory burner and was operated with a precursor-solvent mixture of ethanol and iron(III) nitrate nonahydrate. For studying the relevance of precursor chemistry, LES using an evaporation-limited precursor chemistry model is compared with a model that includes detailed iron chemistry. A further novelty is the inclusion of adsorption in the simulation, which defines a third model for comparison. Sufficient validation is achieved for the undoped LES using experimental data from the literature. A strong impact of the detailed iron chemistry and adsorption is found on the precursor consumption and the aggregate and primary particle formation. Comparing the particle diameters with experimental measurements from the literature and data generated for this work is found unsuitable to asses the precursor chemistry model and revealed an urgent need for future experimental and numerical research. This work serves as a step forward in realizing a reliable model.
Keywords: Flame spray pyrolysis; Iron oxide formation; Large eddy simulation; Method of moments; SpraySyn

Nanoparticle Concentration Measurement in Flame Spray Pyrolysis (Poster) - Massopo, Orlando; Schmid, Hans-Joachim; Gonchikzhapov, Munko; Kasper, Tina
Keywords: Absolute particle concentration; Flame Spray Pyrolysis; SMPS; Mass Spectrometry

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

CDMA: Centrifugal Differential Mobility Analyzer - Ein Messprinzip zur Bestimmung von Multidimensionalen Partikeleigenschaften (Vortrag) - Rüther, Torben; Schmid, Hans-Joachim
Keywords: CDMA